Health equity, care access and quality in headache – part 1 - Claudio Tana; Bianca Raffaelli; Marcio Nattan Portes Souza; Elena Ruiz de la Torre; Daniel Gams Massi; Najib Kisani; David García-Azorín; Marta Waliszewska-Prosół (The Journal of Headache and Pain, 2024)
Abstract Current definitions of migraine that are based mainly on clinical characteristics do not account for other patient’s features such as those related to an impaired quality of life, due to loss of social life and productivity, and the differences related to the geographical distribution of the disease and cultural misconceptions which tend to underestimate migraine as a psychosocial rather than neurobiological disorder. Global differences definition, care access, and health equity for headache disorders, especially migraine are reported in this paper from a collaborative group of the editorial board members of the Journal of Headache and Pain. Other components that affect patients with migraine, in addition to the impact promoted by the migraine symptoms such as stigma and social determinants, are also reported.